Practice of Transradial Approach for Interventional Radiology - Alamer, Sarah Saad; Alazzam, Shujon Mohammed; Aldobikhi , Yousef Ahmed Aldobikhi; Alamer, Lujain Saad; Alzain, Nouf Nasser; Bazuhair, Adeeb Omar (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Interventional radiology (IR) is a specialized field within radiology that diagnoses and treats several conditions through a minimally invasive surgical procedure. The transradial approach (TRA) for endovascular interventions was introduced by Lucian Campeau in 1989. TRA gained great popularity in hemodynamics, with studies demonstrating its safety, feasibility, and superiority compared with the transfemoral approach. The use of the radial artery as the primary access vessel into the arterial system is not a new concept. OBJECTIVE: The objective of the study is to evaluate the practice of TRA among interventional radiologists (IRs). AIM: This study was conducted as a cross-sectional study, targeting interventional radiologists (IRs). The data were collected through an online questionnaire between May 2023 and June 2023. The data were analyzed through the Statistical Package for the Social Sciences. RESULTS: Among 43 interventional radiologists in Riyadh, Saudi Arabia, 39.5% are not performing TRA; reasons for underuse among interventional radiologists (52.9%) include lack of training and (23.5%) distance from the access site; and finally, 17.6% have a potential higher risk for neurological complications; while 60.5% of them are performing TRA, mainly for pelvic procedures (80.8%), followed by hepatic procedures (53.8%). CONCLUSION: In our study, the use of TRA was observed, almost among half of our respondents, and this may relate to reasons such as a lack of appropriate training and distance from the access site. On the other hand, TRA has been proven to have less access site complications and lower mortality. Therefore, better understand the real advantages of TRA and how it can offer higher value in patient care.